The Influence of Precursor Disaggregation During Synthesis of Low-Dimensional AlOOH Structures on their Morphology; Russian Physics Journal; Vol. 57, iss. 12 - Bakina O. V. Olga Vladimirovna; Glazkova E. A. Elena Alekseevna; Svarovskaya N. V. Natalia Valentinovna; Lozhkomoev A. S. Aleksandr Sergeevich; Lerner M. I. Marat Izrailyevich; Psakhie S. G. Sergey Grigorievich (2015, 2015)
Title screen